Measurement inaccuracy of wearable photoplethysmogram in military smartwatch - Ra, Dongyeob; Han, Chankyu; Moon, Sungho; Kim, Kangmin; Lee, Jonghwa (Journal of Advances in Military Studies, 2024)
As the military adopts wearable devices, soldiers use them to check their own health and perform operations. Under these conditions, measurement errors in military smartwatches can significantly affect soldier safety and survival. Photoplethysmogram (PPG) measurement errors may arise from various factors including the physical condition of the user, contact point, and environmental conditions. In particular, soldiers may experience rapid changes in their heart rates owing to intense training and operational activities. In such situations, errors in PPG measurements may pose challenges in accurately assessing the health status of soldiers. Therefore, enhancing PPG measurement functionality using wearable devices is important to accurately assess the health status, improve survivability, and enhance the operational performance of soldiers on the battlefield. Consequently, research and development in this area are necessary. Thus, our study examined the factors contributing to potential PPG measurement errors in smartwatches, assessed the extent of these errors, and discussed approaches to improve and mitigate them.